Learning from Floods: Linking flood experience and flood resilience. (1st October 2020) - Kuang, Da; Liao, Kuei-Hsien
Abstract: It has been argued that learning from flood experience contributes to flood resilience. However, it is unclear what such a learning process involves, and it is debatable whether flood experience always leads to flood resilience. To bridge this research gap, we develop the Learning from Floods (LFF) model to articulate the process of learning from flood experience and how it affects flood resilience. The LFF model suggests that flood experience prompts individual and social learning to give rise to flood-related knowledge, which is subject to learning opportunity, learning motivation, and prior knowledge. Flood-related knowledge could inform flood management and/or other action, which however can be limited by barriers, including information and resource availability, attitude, social capital, and policy barriers. Together, flood-related knowledge and its resulting action are considered the lesson learned, which then affects flood resilience through changing floodability, recoverability, adaptability, and/or transformability. We apply the LFF model to discuss the different learning processes and their respective effects on flood resilience in two environments. It suggests that an environment that is well-protected by flood control infrastructure is not conducive to learning about flood mitigation. Subsequently, we call for learning-based flood mitigation to nurture flood resilience in the face of climate change. Highlights: We propose the Learning from Floods (LFF) model. The LFF model explains how flood experience affects flood resilience via learning. It can be a framework to study learning as a mechanism for nurturing resilience. Lesson learned from flood experience does not always increase flood resilience. We call for learning-based flood mitigation as an alternative paradigm.